First-principles core energies of isolated basal and prism screw dislocations in magnesium. Issue 6 (3rd June 2022) - Dan, Yang; Trinkle, Dallas R.
Abstract : We use first-principles energy density method (EDM) to calculate atomic energies for isolated 〈 a 〉 -type basal and prism screw dislocation cores in Mg and compute line energies and core energy differences. The atomic energy distribution in the dislocations reflect the slip in the cores and the elastic energy further afield. Line energies are computed by summing up atomic energies, from which core energies and energy differences are straightforward to determine. We compare our results with two different classical potentials. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: This work is the first exact, direct calculation of core energies of isolated dislocations using density functional theory via atomic energies, applied to core energy differences in magnesium.